In the Problems of Critical Theory "The Concept of the Text as a Model" - العبدو زكوان جمعة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research attempts to delve into the theoretical critical practice, standing on the necessity of theorizing and its problems, taking the "concept of the text" as a model for the study. What prompted the research to address theoretical critical practice, in the light of criticism criticism, is its realization of the necessity of continuing to work on critical theorizing because of the great tendency in recent studies to apply criticism and theoretical investment to serve it only, so we are faced with repeating the same procedures in these works, and because of its importance In the development of critical visions in the spaces of text theory, which aimed to research the components of the literary text, its aesthetic, and its structural manifestations, with the change of the critical pattern, which turned to the fields of textuality to understand the nature and existence of the text. The research took the descriptive approach as a procedural starting point that aided it by extrapolating the critical opinions that it dealt with, and analyzing them, and responded to observation, analysis, discussion and conclusion of the proposals of contemporary critics who dealt with their visions in defining the "concept of the text", trying in its practice to carry out its subject, seeking to be a good model for theoretical critical practice. The research came out with several results, the most important of which is the realization that the theoretical critical practice involves the student in an abundance of various ramifications according to the references of critics in the Western and Arab fields, and that this practice must continue, despite its problems in the midst of this bifurcation, as it is an effective human activity, necessary in the development of thought.